Electric muscle stimulation (EMS) does not improve anaerobic performance measures during a repeated wingate test - Bajolek, K.; Warne, J. (Research Quarterly for Exercise and Sport, 2023)
Introduction The aim of this study was to examine differences between a control warm-up and an Electric Muscle Stimulation (EMS)-induced warm-up in off-road cyclists when examining anaerobic performance measures from a repeated Wingate test (WAnT).